Pengaruh Keahlian Auditor, Perkembangan Bisnis E-Commerce Dan Teknologi Informasi Terhadap Kebutuhan Jasa Audit E-Commerce - Kiswa, Nur; Su'un, Muhammad; Kalsum, Ummu (Center of Economic Students Journal, 2023)
and information technology on the demand for E-Commerce audit services. The research employs a quantitative approach using a survey method by distributing questionnaires to auditors working at Public Accounting Firms (KAP) in Makassar City. The population in this study includes all auditors from seven Public Accounting Firms registered with the Indonesian Institute of Certified Public Accountants (IAPI), totaling 53 auditors. The sampling technique used is purposive sampling, with criteria including external auditors who have at least one year of experience and have previously conducted E-Commerce audits. Data were analyzed using multiple linear regression. The results of the study indicate that not all auditors in the population have experience in auditing E-Commerce. Partially, the auditor expertise variable does not have a significant effect on the demand for E-Commerce audit services. In contrast, the variables of E-Commerce business development and information technology have a positive and significant influence. Simultaneously, all three variables significantly affect the demand for E-Commerce audit services. This study highlights the importance of digital development and technological support in shaping the need for audits that align with the E-Commerce era.